Radio-Histopathological Spectrum of Ovarian Specimens Following Cystectomy: Radio-Histopathology of Ovarian Cysts - Khaliq, Nagina; Khaliq, Huma; Gulzar, Saima; Yaqoob, Saima; Niazi, Farah Bano; Khalid, Amna (Pakistan Journal of Health Sciences, 2024)
Ovarian cysts can be benign or malignant and requires accurate diagnosis for efficient treatment. Objective: To characterize the radiological and histopathological spectrum of ovarian specimens following cystectomy. Methods: This retrospective study was conducted at Pakistan Atomic Energy Commission General Hospital, Islamabad from 1st April 2022 to 31st December 2022.Eighty patient’s samples from cystectomy patients who were suffering from ovarian cysts were included. Each patient underwent radiological examination before ovarian cystectomy through laparoscopic surgery except two cases of urgent laparotomy. Gross histopathological specimen examination was conducted. The data were analysed using SPSS version 26.0, wherein p value <. 0.05 was considered as significant. Results: The mean age of the patients enrolled in this study was 35.5±5.9 years. Hemorrhagic cysts were having a reticular pattern of internal echoes with soli appearing area with concave margins and no internal flow, while endometrioma cysts were having homogenous low level internal echoes with non-solid component and tiny echogenic foci in the walls. While within the neoplastic cysts 4/8 werehaving cystic external surface and 1/8 presented with ovarian mass.The surface epithelial tumor presented of 2 cases with carcinoma detection on histopathology slides while in the germ cell tumor 1 cases each of strumaovarii, dysgerminoma and mixed germ cell tumor was observed. Conclusions: Surface epithelial tumors were the most common category of ovarian tumors and majority of the cysts were benign cystadenomas. Radiological imaging provides a precise non-invasive tool for categorizing various ovarian cysts and histopathological findings further confirms the exact category of tumors.